Reticulate evolution and humans origins and ecology - Arnold, Michael L. (Michael Lynn) (Oxford : Oxford University Press, 2009)
This work describes the important role that the transfer of genes between organisms has played during the origin and evolution of humans, and the evolution of organisms on which the human species depends for shelter, sustenance and companionship.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Life -- Origin; Evolution (Biology)